Current treatment concepts in intracerebral hemorrhage - Huttner, Hagen; Kuramatsu, J. B. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2017)
In recent years, various important studies investigating the management of intracerebral hemorrhage (ICH) have been published. However, these have not entered guideline recommendations yet. Therefore, essential results are summarized here and the findings are integrated into current treatment concepts.Based on a dedicated literature review and the authors' experience, up-to-date and high-quality investigations were identified.Randomized data and meta-analyses provide evidence that aggressive blood-pressure reduction (targeting a systolic blood pressure <140 mm Hg) appears safe and reduces hematoma enlargement. ICH associated with intake of vitamin K antagonists should be reversed immediately using prothrombin complex concentrates (PCC) and vitamin K, targeting at least international normalized ratio levels below 1.3. For dabigatran-related ICH, an antidote (idarucizumab) is available for reversal, but in ICH under the use of factor Xa inhibitors evidence is poor. However, reversal should be carried out using high-dosed PCC (50 IU/kg PCC). Routine hematoma evacuation surgery cannot be advocated, yet new minimally invasive strategies provide promising results. In patients with acute occlusive hydrocephalus, an external ventricular drain should be placed and utilizing intraventricular lysis appears safe, reduces mortality, and is associated with improved functional outcome. Adding lumbar drainage to this treatment strategy may reduce permanent shunt dependency. The sum of treatment measures and specialized care at high-volume centers improves outcome in patients with ICH.
EVALuna2:22561